2014
DOI: 10.1002/ange.201310983
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Aminocyanation of Alkenes by NCN Bond Cleavage

Abstract: A metal-free, Lewis acid promoted intramolecular aminocyanation of alkenes was developed. B(C 6 F 5 ) 3 activates N-sulfonyl cyanamides, thus leading to a formal cleavage of the NÀCN bonds in conjunction with vicinal addition of sulfonamide and nitrile groups across an alkene. This method enables atom-economical access to indolines and tetrahydroquinolines in excellent yields, and provides a complementary strategy for regioselective alkene difunctionalizations with sulfonamide and nitrile groups. Labeling expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…However, despite extensive effort over the past decades, realizing a catalytic intermolecular carbo­amination of unactivated alkenes has remained a challenge. During the past decade, Wolfe and others have developed a series of palladium(0)-catalyzed intra­molecular carbo­amination methods by using alkene substrates with a tethered nitrogen nucleo­phile (Scheme A) . These transformations are an effective means of accessing various aza­hetero­cycles.…”
Section: Introductionsupporting
confidence: 83%
“…However, despite extensive effort over the past decades, realizing a catalytic intermolecular carbo­amination of unactivated alkenes has remained a challenge. During the past decade, Wolfe and others have developed a series of palladium(0)-catalyzed intra­molecular carbo­amination methods by using alkene substrates with a tethered nitrogen nucleo­phile (Scheme A) . These transformations are an effective means of accessing various aza­hetero­cycles.…”
Section: Introductionsupporting
confidence: 83%
“…We initially chose NCTS, which has been employed in electrophilic cyanation reactions promoted by boron Lewis acids,, as a cyanating reagent to investigate the cyanation of boron enolates derived from chalcone ( 1 a ; Table ) . A brief screening of borane derivatives revealed that the boron enolate prepared using 9‐borabicyclo‐[3.3.1]nonane (9‐BBN) reacted smoothly with NCTS in THF at ambient temperature, thus affording the desired product 2 a in 84 % yield, along with a small amount of the boron complex 2 a ′ as a by‐product (entry 1) .…”
Section: Methodsmentioning
confidence: 99%
“…Douglas and co-workers developed an efficient method allowing the synthesis in excellent yields of the 2,2-disubstituted tetrahydroquinoline 122 via a Lewis acid-promoted intramolecular aminocyanation of alkenes from readily available cyanamide 121 (Scheme ). This transformation may proceed through activation of N -sulfonyl cyanamide group by the Lewis acid B­(C 6 F 5 ) 3 , followed by intramolecular nucleophilic attack of the alkene to the central cyanamide with cleavage of the N–CN bond and vicinal addition of the sulfonamide and nitrile groups across the alkene.…”
Section: Synthesis Of 1234-tetrahydroquinolines By Intramolecular Rea...mentioning
confidence: 99%